SHM_1227381_HST_3D Polygonal Stone Axe - National Historical Museums (National Historical Museums, 2026)
Structured light 3D model of a Polygonal Stone Axe from the Swedish Early Neolithic, collected in the field from Hjulby in Lofta parish, Småland, Sweden and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=407

Link to Sök I Samlingarna

https://samlingar.shm.se/object/C953080E-36C3-485F-BA87-9624E8D6C1AC
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Structured Light Scanning; 3D Model; Museum Object; Dynamic Collections; Hjulby; Swedish Early Neolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi